The geological heritage of the state of São Paulo: potential geosites as a contribution to the Brazilian national inventory - RIBEIRO, Ligia Maria de Almeida Leite (2021)
Having a national geoheritage inventory is essential to plan effective geoconservation strategies. Since 2017, the Geological Survey of Brazil (CPRM) has been carrying out a project aimed at the Inventory of the Brazilian Geological Heritage and defined state coordinations to propose indicative lists of potential geosites based mainly on the scientific value (SV) according to the GEOSSIT platform. For the state of São Paulo, which was the first in Brazil to have a systematic geoheritage inventory, with 137 geosites already defined, this study intends to analyze them to propose some criteria to select the ones to compound the national list. Fifty-seven geosites were chosen according to both SV (≥ 300, following the requirements of GEOSSIT) and representativeness within each geological framework (when SV < 300). We also evaluated the selected geosites in other national initiatives, such as SIGEP (nine geosites) and the Geoparks Project (five geosites). The GEOSSIT public lists show only three of the 57 geosites already registered, a low number considering that these registrations are relevant indicators for the national inventory. The geosites were also analyzed according to the main thematic classification (eight main thematic categories, with a large number in the petrology theme - 35.10%) and general geological context (73.70% in the Mantiqueira, Paraná, and Tocantins provinces and 26.30% in Emerged Phanerozoic Basins - Paraná, Bauru, and São Paulo), according to the parameters available on GEOSSIT. The sites were also evaluated according to typology, being 33 points, 22 areas, and two sections. Regarding the statutory setting, 30% are in fully protected areas, 36% in public or private areas with non-effective statutory protection (APAs, marine land, paleontological sites, etc.), and 34% comprise public or private areas with no protection.